Prevalence of Chlamydia pneumoniae antibodies in patients with acute respiratory infections in Israel. Issue 3 (March 1994) - Ben-Yaakov, M; Lazarovich, Z; Beer, S; Levin, A; Shoham, I; Boldur, I
Abstract : AIMS–To evaluate the prevalence of antibodies to Chlamydia pneumoniae (TWAR) in relation to other aetiological agents of acute respiratory infections in Israeli patients. METHOD–Serum samples from 604 patients (183 children and 421 adults) were collected over three years. Antibodies to C pneumoniae, C trachomatis, and Legionella sp were evaluated using the microimmunofluorescence (MIF) assay. Antibodies to Mycoplasma pneumoniae were detected using the Serodia Myco II test. RESULTS–Antibodies to TWAR were detected in 319 (51.3%) sera. Twenty one patients had MIF results indicative of recent infection. TWAR prevalence and antibody titres in children (aged 1-10 years) were low, gradually increased in teenagers (11-18 years), and were highest in adults and elderly patients. In contrast to the consistently noted TWAR antibody prevalence and serological evidence of recent infection during the study period, a significant decrease in those variables was recorded for C trachomatis. Six patients had serological evidence of recent infection with both C pneumoniae and C trachomatis. The presence of antibodies to Mycoplasma pneumoniae and Legionella sp was tested in 473 of the patients; 29 had antibodies to M pneumoniae and 23 to Legionella sp. Six patients (including five children) had serological evidence of recent infection with M pneumoniae and four with Legionella sp. CONCLUSION–C pneumoniae should be considered in patients with acute respiratory diseases. MIF is the preferred method for monitoring the presence of antibodies to this organism.